2017
DOI: 10.23893/1307-2080.aps.05513
|View full text |Cite
|
Sign up to set email alerts
|

Formulation development and characterization of oxcarbazepine microemulsion for intranasal delivery

Abstract: Nasal cavity is lined by vascularized epithelium which provides larger surface area useful for drug absorption. It has low enzymatic activity in contrast to the di-ABSTRACT The objective of this study was to develop novel intranasal microemulsion containing oxcarbazepine (OXC) for treatment of epilepsy. Optimized ratio of Tween 80: Polyethylene glycol and isopropyl myristate was selected after developing pseudoternary phase diagrams and microemulsions were prepared. The prepared microemulsions were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…We were able to find the average microsphere particle size by dividing the total microsphere size by the total number of microspheres. 13 • Zeta potential Measurements of the Zeta potential were taken using the Malvern Zetasizer, a laser Doppler anemometry-based analyzer that can do multiple angle particle electrophoresis analysis (DTS Ver. 4.10, Malvern Instruments, Malvern, UK).…”
Section: Characterization Of Microspheres • Determination Of Encapsul...mentioning
confidence: 99%
“…We were able to find the average microsphere particle size by dividing the total microsphere size by the total number of microspheres. 13 • Zeta potential Measurements of the Zeta potential were taken using the Malvern Zetasizer, a laser Doppler anemometry-based analyzer that can do multiple angle particle electrophoresis analysis (DTS Ver. 4.10, Malvern Instruments, Malvern, UK).…”
Section: Characterization Of Microspheres • Determination Of Encapsul...mentioning
confidence: 99%
“…In-vitro drug permeation study were performed using the Franz diffusion cell apparatus (EMFDC-6, USA) consisting of donor and accepter chamber separated by Wister rat abdominal skin (shaved) as semipermeable membrane [9,10]. The donor chamber added with 1 gm organogel, acceptor chamber filled with skin pH 6.4-phosphate buffer.…”
Section: In-vitro Drug Permeation and Ex-vivo Flux Studiesmentioning
confidence: 99%
“…The aliquots were analyzed using UV spectrophotometer. 17 The use of a natural membrane is vital for envisage the potential drug release characteristic. Freshly excised goat nasal mucosa was used, procured from the slaughterhouse.…”
Section: Characterization Of Microemulsionmentioning
confidence: 99%
“…ASNM loaded nanostructured lipid carriers reported for a nose to brain targeted delivery to enhance the therapeutic efficacy of ASNM in the treatment of Schizophrenia. Pharmacodynamic and pharmacokinetic studies showed high brain bioavailability, better therapeutic and safety profile of ASNM loaded nanostructured lipid carriers via intranasal route 17 . Also, microemulsion and mucoadhesive microemulsion of ASNM was reported with the increased retention time of formulation due to polycarbophil, which leads to a significant effect on ASNM diffusion through nasal mucosa 21 .…”
mentioning
confidence: 99%